Indentifying the effect of micro friction stir spot welding (µFSSW) parameters on weld geometry, mechanical properties, and metallography on dissimilar materials of AZ31B and AA1100 - Membala, Semuel Boron; Sutresman, Onny Sutyono; Arsyad, Hairul; Syahid, Muhammad; Widyianto, Agus (Eastern-European Journal of Enterprise Technologies, 2022)
Micro-friction stir spot welding (µFSSW) is one type of welding that is suitable for joining lightweight materials. One of the challenges in joining lightweight materials with µFSSW is that the material is easily perforated, or the join is not strong enough, so it is necessary to select the right µFSSW parameters. In this article discusses about investigates the micro-Friction Stir Spot Welding (µFSSW) parameters on weld geometry, mechanical properties, and metallography on dissimilar materials of AZ31B and AA1100. The material thickness of the AZ31B and AA100 is 0.5 mm and 0.32 mm, respectively. The µFSSW tool is made of high-speed steel (HSS) with a pin diameter of 0.25 mm and a shoulder diameter of 0.5 mm. The constant process parameters of the µFSSW joint used, i. e., plunge depth, dwell time plunge rate, and high tool rotational speed of 33,000 rpm. Welding test results include weld geometry, mechanical properties, and metallography. Weld geometry testing to determine the weld nugget diameter. The mechanical properties test was shear tensile test and cross tensile test, while the metallographic test included macrostructure and microstructure observations. The results of the FSSW weld geometry show that at a dwell time of 700 milliseconds and a plunge depth of 600 microns, the weld pin diameter and weld shoulder diameter are close to the pin diameter and the diameter of the shoulder tool used. Dwell time and plunge depth has a significant effect on tensile strength. The maximum shear and cross loads achieved were 387±17 N and 29±2 N, respectively. Intermetallic compounds (IMC) are observed at the interface of the two materials, while a dwell time of 700 milliseconds give the effect of cracks on the inside of the weld